1998
DOI: 10.1172/jci1518
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte apoptosis induced by Fas ligand- expressing ovarian carcinoma cells. Implications for altered expression of T cell receptor in tumor-associated lymphocytes.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(112 citation statements)
references
References 28 publications
4
105
0
3
Order By: Relevance
“…27 The mechanisms involved in tumor-induced downregulation of -chain expression in T cells are still not fully understood, but preliminary data indicate that direct contact with tumor or tumor-derived factors might initiate intracellular caspases in activated T cells, which participate in degradation of the -chain and perhaps other signaling molecules. 18,19 This interpretation fits well with the presence of normal levels of -chain mRNA present in PBL. It should be noted, however, that both patients received the alkylating chemotherapeutic agent temozolomide during the last part of the observation period.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…27 The mechanisms involved in tumor-induced downregulation of -chain expression in T cells are still not fully understood, but preliminary data indicate that direct contact with tumor or tumor-derived factors might initiate intracellular caspases in activated T cells, which participate in degradation of the -chain and perhaps other signaling molecules. 18,19 This interpretation fits well with the presence of normal levels of -chain mRNA present in PBL. It should be noted, however, that both patients received the alkylating chemotherapeutic agent temozolomide during the last part of the observation period.…”
Section: Discussionsupporting
confidence: 70%
“…However, it has been shown that the mRNA levels of the CD3 -chain may remain unaffected, whereas the protein level is decreased. 18,19 For this reason, the CD3 -chain protein level was examined by Western blotting. Data from these analyses clearly demonstrated a substan- tially decreased amount of CD3 -chain protein at time 6 compared to time 1 (Fig.…”
Section: Expression Of the Cd3 -Chain In Pbl And Til During The Coursmentioning
confidence: 99%
“…While patients' T cells may recover expression of z in part during ex vivo stimulation with anti-CD3 mAb, z remained low at 24 or 48 h of culture relative to its expression in normal T cells incubated in parallel. Downregulation of z expression has been reported in T and NK cells of patients with cancers (Zea et al, 1995;Rabinowich et al, 1996Rabinowich et al, , 1998Reichert et al, 1998a, b;Kiessling et al, 1999;Kuss et al, 1999;Whiteside, 1999Meidenbauer et al, 2002;Reichert et al, 2002) and with chronic infections, including HIV (Stefanova et al, 1996;Zea et al, 1998). A transient loss of z expression appears to be a normal consequence of signalling via TcR (Valiutti et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Recent data from our laboratory and other laboratories indicate that tumour-infiltrating and peripheral T cells of many patients with cancer are primed for apoptosis (Rabinowich et al, 1998;Reichert et al, 1998b;Lee et al, 1999;Reichert et al, 2002;, and that the death of effector T cells could be responsible for inadequate antitumour functions. We previously reported that relative to healthy normal controls (NC), patients with cancer have increased proportions of circulating T cells that bind Annexin V (Dworacki et al, 2001;Hoffmann et al, 2002).…”
mentioning
confidence: 89%
“…'Exosomes' from four out of six patients were positive for the presence of B23 by Western immunoblots ( Figure 3C). Since other investigators have suggested the antitumour cellular immune response can be suppressed by the presence of Fas ligand (FasL) (Rabinowich et al, 1998;Whiteside, 2002), shed 'exosomes' were assessed for expression of FasL. All 225 000 P a t i e n t 1 P a t i e n t 2 P a t i e n t 3 P a t i e n t 4 P a t i e n t 5 samples were positive for the intact 41 kDa form of FasL and two were also strongly positive for the 27 kDa cleaved form ( Figure 3B).…”
Section: Characterisation Of Antigens Associated With Membrane Vesiclesmentioning
confidence: 99%